Collided ribosomes form a unique structural interface to induce Hel2‐driven quality control pathways - Ikeuchi, Ken; Tesina, Petr; Matsuo, Yoshitaka; Sugiyama, Takato; Cheng, Jingdong; Saeki, Yasushi; Tanaka, Keiji; Becker, Thomas; Beckmann, Roland; Inada, Toshifumi (The EMBO journal, 2019)
Ribosome stalling triggers quality control pathways targeting the mRNA (NGD: no‐go decay) and the nascent polypeptide (RQC: ribosome‐associated quality control). RQC requires Hel2‐dependent uS10 ubiquitination and the RQT complex in yeast. Here, we report that Hel2‐dependent uS10 ubiquitination and Slh1/Rqt2 are crucial for RQC and NGD induction within a di‐ribosome (disome) unit, which consists of the leading stalled ribosome and the following colliding ribosome. Hel2 preferentially ubiquitinated a disome over a monosome on a quality control inducing reporter mRNA in an in vitro translation reaction. Cryo‐EM analysis of the disome unit revealed a distinct structural arrangement suitable for recognition and modification by Hel2. The absence of the RQT complex or uS10 ubiquitination resulted in the elimination of NGD within the disome unit. Instead, we observed Hel2‐mediated cleavages upstream of the disome, governed by initial Not4‐mediated monoubiquitination of eS7 and followed by Hel2‐mediated K63‐linked polyubiquitination. We propose that Hel2‐mediated ribosome ubiquitination is required both for canonical NGD (NGD RQC + ) and RQC coupled to the disome and that RQC‐uncoupled NGD outside the disome (NGD RQC − ) can occur in a Not4‐dependent manner. Synopsis Ribosome stalling triggers both ribosome‐associated quality control (RQC) of nascent polypeptides and no‐go decay (NGD) of mRNA. Structural and biochemical data show that collided ribosomes form a unique structural unit allowing the Hel2 ubiquitin ligase to operate in both pathways. Hel2‐mediated uS10 ubiquitination and Slh1/Rqt2 are crucial for RQC and NGD induction within a di‐ribosome (disome) unit. Cryo‐EM reveals a unique composite interface between the small subunits of the stalled leading and the following colliding ribosome, which can serve as stalling‐recognition pattern for Hel2. Hel2 preferentially ubiquitinates colliding ribosomes, where Hel2 ubiquitination targets on the respective small subunits congregate in close vicinity. Two distinct NGD branches act differentially on or near a disome unit, one coupled to and one uncoupled from RQC. RQC‐uncoupled NGD is characterized by Not4‐mediated mono‐ubiquitination followed by Hel2‐mediated polyubiquitination of ribosomal protein eS7, resulting in mRNA cleavage upstream of the disome unit. Graphical Abstract Yeast Hel2 ubiquitin ligase functions in both ribosome‐associated protein quality control and canonical mRNA no‐go decay pathways coupled to disome units.